Standarisasi Lini Produksi Divisi Upper di PT. XYZ - Alexandrea Teguh (Jurnal Titra, 2019)
PT. XYZ is a company which produce all kinds of footwear. This company has two manufacturing sectors, Factory 1 and Factory 2. Products that are made by PT. XYZ are divided into two main sections, that is, upper and shoe. Upper is the top side of the product, whilst shoe is the bottom side of the product which combine upper and sole. The research focuses on Upper Department, closing sequence area at Factory 1. The operation processes carried out to produce upper in this area, is done manually. The topic discussed in this journal is standardization of operator’s left hand and right hand movements, along with the design of tools and equipments layout at the work stations. Among 53 observed processes, 34 processes were considered as good while the rest 18 processes had opportunity of improvement. I proposed improvements for these processes. The equipment layout design at the work station is based on standard hand movements so that it helps operators to be more comfortable in doing their jobs. The advantage of the improvements given is that there is increase in the efficiency and effectiveness of the operator so that the operator can more easily achieve the target.